STRATEGI PENGEMBANGAN KAWASAN RAWA DANAU UNTUK MENINGKATKAN EKONOMI BERBASIS KEBERLANJUTAN ANALISIS SWOT DAN KEBIJAKAN - Haryono, Rakhmat; Keizer, Hendriady de (LPPM Politeknik Pajajaran ICB Bandung, 2025)
Rawa Danau, one of the important conservation areas in Banten Province, has high biodiversity and great economic potential, especially in the tourism, renewable energy and sustainable agriculture sectors. However, the development of this area faces challenges such as land use conflicts, limited infrastructure, and the risk of natural disasters. This study aims to analyse the economic potential, challenges and strategies for sustainable management of the area. The methods used include policy, spatial, and SWOT analyses, as well as interviews with stakeholders. The results showed that conservation-based development, infrastructure improvement, and local community involvement can improve community welfare and income. Research recommendations include the development of sustainable tourism, strengthening regulations, and collaboration between the government, private sector and communities. This holistic strategy is expected to support inclusive and environmentally friendly development in Rawa Danau.